Chemotherapy induced carcinoma–adenoma regression in the caecum. Issue 3 (27th February 2009) - Abela, J E; Wright, D M; Hennessy, A; Roberts, F; Anderson, J R
Abstract : The case of a male patient with synchronous oesophago-gastric junction (OGJ) and caecal adenocarcinomas is reported. His management is described, particularly the administration of neoadjuvant chemotherapy targeting his upper gastrointestinal cancer. Synchronous gastrectomy and hemicolectomy were performed. Histopathological examination of the surgical specimen confirmed the OGJ cancer but only identified a caecal adenoma. This is believed to be the first description of chemotherapy induced reversal of the adenoma–carcinoma sequence.